Mentoring in a dual career in sports: systematic review - Martinsone, S. S. (LASE Journal of Sport Science, 2024)
Aim. The purpose of this systematic review was to explore and analyze the scientific literature on mentoring in the context of dual careers in sports. This analysis included a detailed examination of the methodologies and approaches employed in mentoring processes, as well as an evaluation of the research outcomes. Special attention was given to how mentor competencies and skills are applied to support athletes in their efforts to successfully manage and integrate their sporting and academic endeavors. The review aimed to identify effective strategies and highlight the critical role of mentoring in facilitating the dual career pathways of athletes, especially within European contexts. This work contributes to understanding the necessary frameworks and support systems required for optimizing dual career outcomes in sports.